Análise tomográfica da articulação temporomandibular no tratamento com Herbst em adulto jovem - Maia, Savana de Alencar [UNESP]; Dib, Luana Paz Sampaio [UNESP]; Landázuri, Denise Rocha Goes [UNESP]; Raveli, Taisa Boamorte; Raveli, Dirceu Barnabé [UNESP] (My University, 2010)
Class II malocclusion features a high prevalence in Brazil, being considered as a routine in orthodontic clinics. A number of appliances are shown in the literature in order to correct Class II malocclusion with mandibular retrusion. Herbst´s fixed functional appliance, idealized by Emil Herbst (1905) and reintroduced, in the 1980´s, by Hans Pancherz is highlighted for maintaining the mandible continuously advanced, showing a shorter active treament time, an immediate esthetic impact on the facial profile, as well as requiring no patient´s commitment. Recent researches indicate the use of this appliance in individuals after pubertal growth surge. The aim of the present study is to show the orthodontics practitioner the option to use this appliance so as to treat Class II in individuals after the growth surge, obtaining satisfactory outcomes and further Class II correction.

O aparelho funcional fixo Herbst idealizado por Emil Herbst (1905) e reintroduzido, na década de 1980, por Hans Pancherz; destaca-se por manter a mandíbula avançada de modo contínuo e pesquisas recentes indicam a utilização deste aparelho em indivíduos após o surto de crescimento pubertário. O objetivo da apresentação deste caso clínico é elucidar os mecanismos de adaptação das ATMs, por meio de imagens da tomografia cone-beam, de um paciente adulto jovem (18 anos e sete meses), portador de má-oclusão de Classe II, Divisão 1, associada a retrognatismo mandibular, tratado com aparelho de Herbst bandado durante oito meses. Os resultados mostraram imagens das ATMs que sugerem remodelação condilar e fossa glenoide. A má-oclusão foi corrigida mostrando-se estável dois anos pós-tratamento. Diante dos resultados obtidos pode-se concluir que o aparelho de Herbst é uma boa opção no tratamento da má-oclusão de Classe II associada a retrognatismo mandibular, em indivíduos adultos jovens, não produzindo efeitos deletérios nas ATMs em avaliação a curto prazo.
Analysis cone beam of temporomandibular joint in young adult in Herbst appliance
Keywords: Temporomandibular joint; Tomography; Orthotic devices; Articulação temporomandibular; Tomografia; Aparelhos ortopédicos